Structural behaviour assessment and material characterization of traditional adobe constructions - Varum, H. (2012)
In Aveiro district, adobe can be found with abundance in rural and urban buildings, many of which are of cultural, historical and architectonic recognized value. A great number of the existing adobe constructions present pronounced structural damage, which results, in great part, from the lack of maintenance and the limited available knowledge concerning the mechanical behaviour of these structures. It is thus recognised the urgency for the development of research work in the structural analysis and strengthening of this important legacy. This work is of great value to the reduction of the seismic risk associated to these adobe constructions. The University of Aveiro has been developing studies to help filling the technical information gap concerning the structural behaviour of existing adobe constructions. Cylindrical adobe specimens were subjected to compressive and “splitting” tests, and prismatic mortar specimens were subjected to compressive tests. Small wallets, constructed with materials representative of those found in existing adobe constructions, were subjected to compression tests, perpendicularly and diagonally to the bed joints. The structural non-linear response of adobe walls has also been investigated in a series of full-scale tests, in the laboratory and in situ, with imposed horizontal cyclic displacements. This article describes the studies carried out and discusses the principal results. These studies aim to establish a basis of knowledge that can support the interpretation of structural pathologies, calibration of numerical models, structural safety assessment, and design of strengthening solutions for the existing adobe constructions, and even support the design and execution of new edifications.